Education and Implementation of Household Composting System to Reduce Waste Generation in Kedungsuren Village, Kaliwungu Selatan, Kendal. - Aden Paiq Muntaz; Muhammad Ilham Prasetya; Irgi M. Aqil Daeng Masiga; Eko Setyo Nugroho; Muhammad Zacky Sulthoni; Nabila Mey Nur Hardini; Fatimah Nisa Royyani; Dwi Ayu Novita; Nur Hijratun Nafiah; Itsna Cholifatun Nisa; Nadya Sya’ada; Anisa Badriyah; Avika Fitriana Assari; Shovi Zaidatul Ma’rifah; Aulia Najwa Zaen; Najichah M.H (Lembaga Pengembangan Kinerja Dosen, 2024)
The program